Clinical Outcomes and Independent Risk Factors for 90-Day Mortality in Critically Ill Patients with Respiratory Failure Infected with SARS-CoV-2: A Multicenter Study in Turkish Intensive Care Units - Gundogan, Kursat; Akbudak, Ismail Hakki; Hanci, Pervin; Halacli, Burcin; Temel, Sahin; Gullu, Zuhal; Topeli, Arzu (Galenos Publ House, 2021)
Background: There are limited data on the long-term outcomes of COVID-19 from different parts of the world. Aims: To determine risk factors of 90-day mortality in critically ill patients in Turkish intensive care units (ICUs), with respiratory failure. Study design: Retrospective, observational cohort. Methods: Patients with laboratory-confirmed COVID-19 and who had been followed up in the ICUs with respiratory failure for more than 24 hours were included in the study. Their demographics, clinical characteristics, laboratory variables, treatment protocols, and survival data were recorded. Results: A total of 421 patients were included. The median age was 67 (IQR: 57-76) years, and 251 patients (59.6%) were men. The 90-day mortality rate was 55.1%. The factors independently associated with 90-day mortality were invasive mechanical ventilation (IMV) (HR 4.09 [95% CI: [2.20-7.63], P<.001), lactate level >2 mmol/L (2.78 [1.93-4.01], P<.001), age >= 60 years (2.45 [1.48-4.06)], P<.001), cardiac arrhythmia during ICU stay (2.01 [1.27-3.20], P=.003), vasopressor treatment (1.94 [1.32-2.84], P=.001), positive fluid balance of >= 600 mL/day (1.68 [1.21-2.34], P=.002), PaO2/FiO(2) ratio of <= 150 mmHg (1.66 [1.18-2.32], P=.003), and ECOG score >= 1 (1.42 [1.00-2.02], P=.050). Conclusion: Long-term mortality was high in critically ill patients with COVID-19 hospitalized in intensive care units in Turkey. Invasive mechanical ventilation, lactate level, age, cardiac arrhythmia, vasopressor therapy, positive fluid balance, severe hypoxemia and ECOG score were the independent risk factors for 90-day mortality.
Keywords: New-York-City; Fluid Balance; Covid-19